The Judiciary Interpretation of the Substantive Criminal Text and its Judicial Problematic Issues - Rahal, Mohamed tahar (Journal of Human Sciences, 2025)
The judiciary interpretation is a mental and cognitive activity that relates to jurisprudence, the magistrate has recourse to it when he is in a situation to apply a criminal rule for a particular case, for the purposes of understanding the law maker’s intent, provided the observance of the principle of the legality of offences and punishments is respected, together with the restricted interpretation of the criminal text. The magistrate ought to omit referring to analogy, and should interpret doubt for the benefit of the accused. The formulation of criminal texts in an ambiguous way or in a way creating contradiction between legal provisions is one of the most problematic issues regarding judiciary interpretation. The other problematic issue is the misinterpretation by the magistrate of the criminal text.